Customizing software. - Ferro, Teri; Daniel, Mike (American City & County, 2006)
This article reports on the development of systems that matches existing processes and operational changes in small local government. New systems are being created on platforms that put the power of customization in the hands of any software user. Understanding some of the recent technological capabilities can help local government managers significantly improve their operations.